Dosimetric characteristics of fabricated germanium doped optical fibres for a postal audit of therapy electron beams - Abdullah, N.; Bradley, D. A.; Nisbet, A.; Kamarul Zaman, Z.; Deraman, S. S.; Mohd Noor, N. (Elsevier, 2022)
The dosimetric characteristics of germanium (Ge) doped optical fibres are investigated as a potential dosimetric alternative for electron beam therapy postal audits. The dosimetric characteristics of 6 mol% Ge-doped optical fibres fabricated as cylindrical fibres (CF) and flat fibres (FF) are established in terms of signal fading, linearity of dose-response, beam energy- and dose rate dependence. Pilot electron beam therapy audit study irradiations are made with a linear accelerator located at the Royal Surrey County Hospital, applying International Atomic Energy Agency (IAEA) standard irradiation procedures for reference and non-reference conditions. Results for the CF and FF show fading of 26% and 20% respectively at 120 days post-irradiation. For a 6 MeV electron beam the dose-response is observed to be linear over the dose range 1–3 Gy, the least determination coefficient, R2, being 0.985. The results of the electron beam therapy audit are within the tolerance limit of 5% recommended by the International Commission on Radiation Units and Measurements (ICRU) Report No. 24, with a maximum deviation of 4% for FF at a 6 MeV electron beam under non-reference conditions. In conclusion, the fabricated Ge-doped optical fibres are seen to offer suitability for use as an alternative dosimeter to TLD-100 in electron beam therapy postal audit.